A short glimpse on promising pharmacological effects of Begenia ciliata - Pokhrel, Priyanka; Parajuli, Rishi Ram; Tiwari, Amish Kumar; Banerjee, Janmajoy (Journal of Applied Pharmaceutical Research, 2014)
Bergenia ciliata is a potent indigenous folk medicine that has been proved fruitful in the treatment of various adverse conditions of the body. The major chemical constituents of plant include tannic acid, gallic acid, glucose, metarbin, albumen, bergenin, (+)-catechin, gallicin. Bergenia ciliata was subjected to bioactivity analysis. The plant has antitussive, antiulcer, antioxidant, antibacterial, hypoglycemic, toxicological activity. It was observed that root and leaves extract were promising as antifungal agent. The root and leaves extract were effective against Microsporum canis, Pleuroetus oustreatus and Candida albicans.Â Â  All the extracts except chloroform extract of root and leaves of Bergenia ciliata were found to possess hypoglycemic activity in Streptozotocin (STZ) treated rats. The methanolic extract exhibited significant anti-tussive activity in a dose-dependent manner. B. ciliata bear potent anti-neoplastic activities that may have prospective clinical use as precursor for preventive medicine. Methanolic and aqueous B. ciliata rhizome extracts were found to possess antioxidant activity, including reducing power, free radical scavenging activity and lipid peroxidation inhibition potential. Bergenia ciliata extracts exhibit a narrow spectrum antibacterial activity. The results obtained thus suggest that extracts of B. ciliata have promising therapeutic potential and could be considered as potential source for drug development by pharmaceutical industries.